Funções executivas na infância : bateria de avaliação informatizada com escala de percepção parental - Cordeiro, Andriely dos Santos (2024)
This thesis aimed to investigate executive functions (EF) in children. The Child Executive Functions Assessment Battery (Bateria de Avaliação das Funções Executivas Infantis - BAFE-inf), a tool composed of computerized tests that assess inhibition, working memory, and cognitive flexibility, in addition to a scale based on parental perception, was used. The three studies that make up the thesis analyzed different aspects of EF in children with typical and atypical development, as well as evidence of the battery’s validity and reliability. The first study focused on the content validity of the BAFE-inf and involved seven experts and 22 participants from the target population (children and parents). The clarity, relevance, and design of the items were evaluated, with results indicating high validity indices and a high percentage of agreement. Suggestions for improvements in the items and layout were implemented, and the BAFE-inf showed evidence of content-based validity for assessing EF in children. The second study investigated the internal consistency and reliability of the BAFE-inf, involving 276 children aged 6 to 10. The results indicated that the measures of inhibition and working memory exhibited a bifactorial structure, while flexibility and the parental perception scale were unifactorial. Most measures showed adequate reliability indices, confirming the internal consistency of the battery. The third study compared EF between children with typical development (n=276) and atypical development (n=29). Children with typical development performed better in inhibition and cognitive flexibility, and showed fewer daily difficulties based on parental perception, while working memory did not differentiate between the groups. Children's performance improved with age. The three studies confirm that EF development occurs progressively in children and that the BAFE-inf provides evidence of validity and reliability, as well as the ability to differentiate between groups with typical and atypical development. These findings highlight the importance of early EF assessment for appropriate referral of children with difficulties to specialized professionals.